Notch Signaling Pathway and Endocrine Resistance in Breast Cancer - Bai, Jing-Wen; Wei, Min; Li, Ji-Wei; Zhang, Guo-Jun (Frontiers in Pharmacology, 2020)
Nearly 70% of breast cancers express the estrogen receptor (ER) and are hormone-dependent for cell proliferation and survival. Anti-estrogen therapies with aromatase inhibitors (AIs), selective estrogen receptor modulators (SERMs) or selective estrogen receptor down regulators (SERDs) are the standard endocrine therapy approach for ER positive breast cancer patients. However, about 30% of patients receiving endocrine therapy will progress during the therapy or become resistant eventually. The intrinsic or acquired endocrine resistance has become a major obstacle for endocrine therapy. The mechanism of endocrine resistance is very complicated and recently emerging evidence indicates dysregulation of Notch signaling pathway contributes to endocrine resistance in breast cancer patients. The potential mechanisms include regulation of ER, promotion of cancer stem cell (CSC) phenotype and mesenchymal cell ratio, alteration of the local tumor microenvironment and cell cycle. This review will summarize the latest progress on the investigation of Notch signaling pathway in breast cancer endocrine resistance.